Aggregate Indices Method in Soil Quality Evaluation Using the Relative Soil Quality Index - Ho Ngoc Pham; Hai Xuan Nguyen; Anh Ngoc Nguyen; Diep Ngoc Tran (Applied and Environmental Soil Science)
This paper presents a new approach to assess the soil quality by aggregate indices using the Relative Soil Quality Index (RSQI) proposed by Ho Ngoc Pham. RSQI is integrated from the individual indices into a simple formula for overall assessment of the soil quality. RSQI is different from other approaches. Particularly, the individual indices and the weighting factors of Pham are calculated from the analytical laboratory data and the environmental standards, respectively, and not self-regulated as in methods of some other authors. In this paper, the authors applied the RSQI to assess the Soil Environmental Quality of rice intensive cultivation areas through a case study in Haiduong province in 2013. The RSQI is calculated for sampling points in 12 districts and simulated the Soil Environmental Quality on GIS map. The results show that the Soil Environmental Quality of rice intensive cultivation areas in Haiduong is predominantly divided into three levels: good, moderate, and poor. According to the report of General Statistics Office for Haiduong province, rice intensive cultivation areas in 2013 achieved a relatively high average rice yield of 5.90 tonnes per hectare; it means actual soil properties are in line with results of the research.